An Investigation into the Anti-Aggregation Potential of Swietenia macrophylla Triterpenoid on Bovine Serum Albumin: Docking and RMSF - Bayu Fajriansyah Al-Khairi; Mukhammad Asy'ari; Agustina L. N. Aminin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Protein aggregation, caused by environmental factors, can lead to neurodegenerative diseases. Hydrophobic compounds like latrepirdine are used in medical treatments like anti-Parkinson’s and Huntington’s diseases. Swietenia macrophylla contains abundant hydrophobic compounds from the triterpenoid group, but their anti-aggregation potential has not been reported. This study investigates the hydrophobic interactions and anti-aggregation potential of triterpenoid compounds, including swietenine, swietenolide, khayasin T, beta-sitosterol, and stigmasterol, against bovine serum albumin (BSA). Latrepirdine is employed as the control compound. In silico methods, molecular docking and molecular dynamics showed potential in clusters 1 and 2, with swietenine having a more stable RMSF value than latrepirdine. The study found four clusters with all ligands, with cluster 1 being the earliest protein opening area. Mahogany seed triterpenoid compounds have potential in cluster 1 (51-67%), while cluster 2 has 37-46%. In cluster 2, they have an advantage over latrepirdine (2%). Stigmasterol and beta-sitosterol are spread across the clusters. The swietenine compound has a more stable RMSF value than latrepirdine. This suggests that mahogany seed triterpenoid compounds have potential as anti-aggregation agents.